2015
DOI: 10.3329/jdmc.v23i2.25325
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome in Ischemic Heart Disease Patients

Abstract: Ischemic heart disease (IHD) isIn the present study the prevalence of metabolic syndrome in IHD patients was found to be 30%. Prevalence was higher in less then 50 years of age group. The prevalence was also higher in female than male.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…16 An study in our neighboring country showed the prevalence 29.9% and 30% respectively. 6,16 Zalunas et al found the MetS more prevalent in women than men 70.2% to 52.6%. 18 Our study prevalence very near to study that also based on modified ATPlll criteria showed prevalence or MetS was 50%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 An study in our neighboring country showed the prevalence 29.9% and 30% respectively. 6,16 Zalunas et al found the MetS more prevalent in women than men 70.2% to 52.6%. 18 Our study prevalence very near to study that also based on modified ATPlll criteria showed prevalence or MetS was 50%.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of IHD markedly increases with the presence of metabolic syndrome. 6 Our study was aimed to find the frequency of metabolic syndrome in IHD patients. We enrolled the IHD patients admitted in CCU of our hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation